Refugee Children's Early Development during Attendance of Specialized Preschool Programs and Transition into First Grade in Germany. Issue 8 (17th November 2022) - Busch, J.; Cabrera, N.; Ialuna, F.; Buchmüller, T.; Leyendecker, B.
ABSTRACT: Research Findings : We assessed socio-emotional behavior, nonverbal reasoning, German receptive language, and motor skills of refugee children attending early childhood development [ECD] programs and of those who did not ( N = 207, mean age = 69.4 months). Young refugee children overall demonstrated lower levels of development and more socio-emotional behavior problems. Attendance of preschool-based ECD programs was inconsistently linked to better outcomes. Only moderate improvements in German receptive language skills could be supported across different methodological approaches. Although socio-emotional problems of refugee children attending ECD programs persisted on high levels, those children showed overall fewer problems when compared to non-attenders at the transition to first grade, especially less hyperactivity/inattention and more prosocial behavior. Practice or Policy : Our study supports that refugee experiences during early childhood are linked to lower developmental learning foundations. Specialized ECD programs for refugees can compensate a general shortage in regular ECD services in times of increased demands. Such programs thus increase the chances of refugee children to keep pace academically with their non-refugee peers. However, as specialized programs for refugee children establish a non-inclusive route in the early education sector of Germany, they still have to empirically prove quality and promoting effects on the children's ECD.